A New Approach of Morgan-Voyce Polynomial to Solve Three Point Boundary Value Problems - Kashem, Bushra Esaa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
In this paper, a new procedure is introduced to estimate the solution for the three-point boundary value problem which is instituted on the use of Morgan-Voyce polynomial. In the beginning, Morgan-Voyce polynomial along with their important properties is introduced. Next, this polynomial with aid of the collocation method utilized to modify the differential equation with boundary conditions to the algebraic system. Finally, the examples approve the validity and accuracy of the proposed method.